Probing Galactic Outskirts with Dragonfly. Issue Volume 11:Issue S321(2015) (21st March 2017) - Abraham, Roberto; Merritt, Allison; Zhang, Jielai; van Dokkum, Pieter; Conroy, Charlie; Danieli, Shany; Mowla, Lamiya
Abstract: We describe the challenges inherent to low surface brightness imaging and present some early results from the Dragonfly Nearby Galaxies survey. Wide field, ultra-low surface brightness imaging (μ g > 31 mag arcsec −2 ) of the first eight galaxies in the survey reveals a rich variety in the distribution of stars in the outskirts of luminous nearby galaxies. The mean stellar halo mass fraction is 0.009 ± 0.005 with a peak-to-peak scatter of a factor of > 100. Some galaxies in the sample feature strongly structured halos resembling that of M31, but three of the eight galaxies have halos that are completely undetected in our data. We conclude that spiral galaxies as a class exhibit a rich variety in stellar halo properties, implying that their assembly histories have been highly non-uniform. While the outskirts of some galaxies are dominated by halos with the rich substructures predicted by numerical simulations, in other cases the outermost parts of galaxies are simply the extrapolated smooth starlight from enormous stellar disks that closely trace neutral gas morphology out to around 20 scale lengths.